Triacontyl p-coumarate: An inhibitor of snake venom metalloproteinases - Mendes, M. M.; Vieira, S. A P B; Gomes, M. S R; Paula, V. F.; Alcântara, T. M.; Homsi-Brandeburgo, M. I.; Dos Santos, J. I. [UNESP]; Magro, A. J. [UNESP]; Fontes, M. R M [UNESP]; Rodrigues, V. M. (Elsevier, 2013)
Snake venom metalloproteinases (SVMPs) participate in a number of important biological, physiological and pathophysiological processes and are primarily responsible for the local tissue damage characteristic of viperid snake envenomations. The use of medicinal plant extracts as antidotes against animal venoms is an old practice, especially against snake envenomations. Such plants are sources of many pharmacologically active compounds and have been shown to antagonize the effects of some venoms and toxins. The present study explores the activity of triacontyl p-coumarate (PCT), an active compound isolated from root bark of Bombacopsis glabra vegetal extract (Bg), against harmful effects of Bothropoides pauloensis snake venom and isolated toxins (SVMPs or phospholipase A2). Before inhibition assays, Bg or PCT was incubated with venom or toxins at ratios of 1:1 and 1:5 (w/w; venom or isolated toxins/PCT) for 30 min at 37 °C. Treatment conditions were also assayed to simulate snakebite with PCT inoculated at either the same venom or toxin site. PCT neutralized fibrinogenolytic activity and plasmatic fibrinogen depletion induced by B. pauloensis venom or isolated toxin. PCT also efficiently inhibited the hemorrhagic (3MDH-minimum hemorrhagic dose injected i.d into mice) and myotoxic activities induced by Jararhagin, a metalloproteinase from B. jararaca at 1:5 ratio (toxin: inhibitor, w/w) when it was previously incubated with PCT and injected into mice or when PCT was administered after toxin injection. Docking simulations using data on a metalloproteinase (Neuwiedase) structure suggest that the binding between the protein and the inhibitor occurs mainly in the active site region causing blockade of the enzymatic reaction by displacement of catalytic water. Steric hindrance may also play a role in the mechanism since the PCT hydrophobic tail was found to interact with the loop associated with substrate anchorage. Thus, PCT may provide a alternative to complement ophidian envenomation treatments. © 2012 Elsevier Ltd. All rights reserved.
Keywords: Bombacopsis glabra (Bombacaceae); Bothropoides pauloensis; Bothrops; Chestnut of Maranhão; Jarharagin; Medicinal plant; Metalloproteinase; Plant anti-snake venom; Snake venom; coumaric acid; metalloproteinase; plant extract; snake venom; animal; chemistry; drug antagonism; enzymology; metabolism; Animals; Coumaric Acids; Metalloproteases; Plant Extracts; Snake Venoms; Animalia; Bombacopsis; Bothrops jararaca; Malvaceae; Mus; Serpentes; Viperidae